Cámara estática de vigilancia con detección de movimiento usando imágenes empleado en labview - León, J. (2010)
This work is a project you want to provide users without a costly system of security and safety to their homes, businesses, residential and industrial sectors, firms, banks, hotel hallways, parking lots and an unlimited range of places where is desired to provide security, a proposal which is practical and very common tools used today's technology gives us are like a desktop or laptop and a USB webcam. The main goal is to have the security administration to the hands of users who desire, easy management of the same and optimization of storage resources is achieved through motion detection, each time only motion is detected in the area you wish to monitor or security system to begin to take photographs and turn to the log out of the camera have a video of concatenated images in addition to a report in a spreadsheet which may know the time at which occurred the respective alarms and detections.